Terapia vocal de base e sons nasais: efeitos sobre disfonias hipercinéticas - Andrade, Simone Rattay (2007)
The proposal of the present study aimed to verify the effects of a speech therapy program that included the use of vocal orientation, adaptation of the breathing function and the technique of nasal sounds. It was investigated three individuals female with otolaryngological diagnosis of edema in the arytenoids area, small nodule in the right vocal fold, medium-subsequent rift and hemorrhagic points in both vocal folds; nodule in the left vocal fold and rift in the medium third; larynx without alterations; respectively. Otolaryngologists first examined people completely (ears, nose and throat), being also accomplished the videolaryngoscopy exam, for the visualization of the larynx s conditions and structures. After that, they were sent to the audiologic exam, in order to discard any hearing disorder. Later, the individuals without any hearing alterations were sent to individual speech therapy evaluations, in a private clinic, before the beginning of the treatment. Anamnesis, orofacial exam, corporal evaluation, and vocal evaluation were accomplished. During the treatment, they received orientations of vocal tract anatomy and physiology, voice cares, including therapy of water ingestion, breathing and posture aspects, besides of nasal sounds technique. The orientations and exercises done in the speech therapy sessions (with approximate time of 30 minutes), were also accomplished at home by the patients for more four days, once a day, for four months, in a total of sixteen sessions. After that, they were revalued to identify possible changes in the laryngeal and vocal aspects. The vocal data before and later accomplishment of the therapeutic program were submitted to the acoustics analyses, accomplished with the use of the Multi Dimensional Voice Program of Kay Elemetrics program, and perceptive-hearing accomplished by three judges (three speech therapy specialist in voice). The analysis of the results evidenced that the nasal sound, ally to the base therapy, propitiated: edema disappearance and of hemorrhagic points; decrease of medium-subsequent vocal rifts and nodules; better vibration of the mucous wave of the vocal folds; postural adaptation and kind of breathing; better breathing, speech and articulation coordination; better resonant focus, voice type, and loudness; pitch and fundamental frequency discreetly more acute; decrease of the noise and of the vocal instability. We came to the conclusion that the speech therapy base (breathing and posture orientation and adaptation), with emphasis in nasal sounds technique, promoted a positive effect on the structures of the vocal folds and on the vocal quality as a whole.